Neuroprotective effect of cedrol in a male rat model of Parkinson's disease - Fatemeh Forouzanfar; Mahmoud Hosseini; Amir Mahmoud Ahmadzadeh; Ali Mohammad Pourbagher‐Shahri (Physiological Reports)
Abstract Cedrol is a natural sesquiterpene subgroup of terpenes with antioxidant and anti‐inflammatory properties. This study evaluated the effect of cedrol on the 6‐hydroxydopamine (6‐OHDA) rat model of Parkinson's disease (PD). Unilateral injection of 6‐OHDA was performed to induce the PD model. Cedrol at 10 mg/kg and 20 mg/kg was administrated. The rotarod test, apomorphine‐induced rotational test, and open field tests assessed motor function, while the passive avoidance test was used to evaluate cognitive function. Furthermore, striatal levels of malondialdehyde (MDA) and total thiol, and SOD (superoxide dismutase) activity were measured. The induction of lesion led to a significantly higher number of rotations in the apomorphine‐induced rotational test, lower maintenance in the rotarod test, as well as a shorter delay for entering into and a longer duration of time spent in the dark chamber in the passive avoidance test, versus the control group. It also enhanced the striatal levels of MDA and diminished the striatal SOD activity and level of total thiol. Administration of cedrol significantly improved behavioral tests and biochemical assays. Cedrol could benefit cognitive and motor functions in a rat model of PD. Its antioxidant properties might mediate these effects.